2015
DOI: 10.4172/2165-8064.1000222
|View full text |Cite
|
Sign up to set email alerts
|

Find the Suitable Warp Tension to get the Best Resistance for Jacquard Fabric

Abstract: Citation: Karnoub A, Kadi N, Azari Z, Bakeer ES (2015) Find the Suitable Warp Tension to get the Best Resistance for Jacquard Fabric. J Textile Sci Eng 5: 222.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…The study of warp tension mechanics dates from very early work reported by Schlichter [23] . Zitouni and Karnoub [13,30] , disused the effect of different warp tension for Chenille Fabric using Jacquard loom by using different weave density using polyester yarns, the same results can conclude in three points: first relation; there is an inverse relationship between weft density and warp tension. Second relation, is a direct relationship between weave float and warp tension also weft count and warp tension relation.…”
Section: Introductionmentioning
confidence: 87%
“…The study of warp tension mechanics dates from very early work reported by Schlichter [23] . Zitouni and Karnoub [13,30] , disused the effect of different warp tension for Chenille Fabric using Jacquard loom by using different weave density using polyester yarns, the same results can conclude in three points: first relation; there is an inverse relationship between weft density and warp tension. Second relation, is a direct relationship between weave float and warp tension also weft count and warp tension relation.…”
Section: Introductionmentioning
confidence: 87%
“…In general, equipment speed and tension are important factors for determining the quality of WIP in warping, beaming, sizing, and weaving. Excessively high tension may cause yarns to fracture, whereas excessively low tension may cause yarn breakage [6,7]. Equipment settings account both for the type of process and the composition of raw materials.…”
Section: Iiot and Textile Manufacturingmentioning
confidence: 99%
“…During weaving is essential to perfectly set up a machine for perfect weaving as indicated in El-Tntawi Ahmed Ramadan’s (2021) paper which studied the fundamentals of warp tension and its role in linen fabric production. The study of warp tension mechanics dates from very early works (Azari et al , 2015; Karnoub et al , 2015; Karnoub et al , 2017; Neogi, 2016; Sheikhzadeh et al , 2007). It can fully summarize that to ensure efficient working of the loom and desired qualities of the cloth produced; the warp yarns are required to be fed up to the required extent and under a certain optimum tension in each pick, determined by the type of cloth to be woven, throughout the weaving out of the warp beam.…”
Section: Introductionmentioning
confidence: 99%